Fox Crossing - Metz, Melinda (Kensington Publishing Corp., 2020)
"In the mountain village of Fox Crossing, Maine, everyone knows the story of The Fox. According to local legend, one of the town's founders crossed paths with a curious-looking fox with a distinctive white ear and paw. The unusual fox sighting not only inspired the town's name, it sparked a fantastical piece of folklore that's been passed down for generations. Some people say that whoever sees The Fox will be rewarded with good fortune, love, and happiness. Others say it's just a silly folk tale . . . Annie Hatherley doesn't believe The Fox legend--even though it was her great-great-great-grandmother who spotted the critter centuries ago. But now it's part of Annie's legacy, along with her family business, Hatherley's Outfitters. For years, Annie's been selling gear to hikers on the Appalachian Trail. But she's never seen The Fox--until now. Out of nowhere, this little white-eared vixen leads her to Nick Ferrone, a woefully unprepared hiker who needs her help. The Shoo Fly Bakery owner also spots the sly creature--who takes him to a homeless dog that needs his love. Annie can't deny that something magical is happening--because she's starting to fall for a certain foxy hiker named Nick..."--Provided by publisher.